γδ T cells in diabetes mellitus: dual roles and therapeutic implications - Wang, Bing; Li, Qi; Wang, Qiuyue (Frontiers in Immunology, 2025)
Diabetes mellitus is primarily categorized into type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM), which exhibit distinct pathogenic mechanisms. T1DM is characterized by an absolute deficiency of insulin secretion, predominantly resulting from the autoimmune-mediated destruction of pancreatic beta cells. In contrast, T2DM arises from a combination of insulin resistance in peripheral tissues and a compensatory insulin secretory response that ultimately becomes inadequate. The pathogenesis of diabetes mellitus is orchestrated through bidirectional crosstalk between autoimmune aggression and metabolic derangement. γδ T cells, innate-like lymphocytes bridging innate and adaptive immunity, play pivotal roles in tissue homeostasis, inflammation, and immunity through cytokine production and cytotoxicity. This review comprehensively examines the dual roles of γδ T cells across diabetes mellitus types. Furthermore, γδ T cells contribute to diabetic complications and are profoundly affected by the diabetic milieu, leading to defective anti-infection and anti-tumor immunity. We discuss emerging therapeutic strategies targeting γδ T cells or their effector pathways and highlight key knowledge gaps regarding subset-specific functions, dynamic changes during disease progression, and tissue-resident γδ T cell roles. Elucidating these mechanisms may provide a strong foundation for developing novel γδ T cell-based immunotherapies for diabetes mellitus and its complications.